DEVELOPMENT OF POP UP LEARNING MEDIA BOOk PANCASILA EDUCATION CULTURAL DIVERSITY MATERIAL FOR GRADE IV STUDENTS OF SD NEGERI 016 KUANTAN SINGINGI - Hestin Tri Putri Rahmadani; Siti quratul ain (SOSIOEDUKASI, 2026)
This research is motivated by the suboptimal use of learning media in the subject of Pancasila Education, cultural diversity material in elementary schools. The learning process is still dominated by lecture methods and the use of package books so that students are less active, easily bored, and have difficulty understanding the material. This research aims to develop a learning media for the Pop Up Book of Pancasila Education, cultural diversity material for grade IV students of SD Negeri 016 Kuantan Singingi and to determine the level of validity and practicality of the developed media. This research uses the Research and Development (R&D) method with the ADDIE development model which is limited to the analysis, design, and development stages. The research subjects consist of grade IV teachers, grade IV students, and validators who include linguists, material experts, and media/design experts. Data collection techniques are carried out through interviews and questionnaires. The data was analyzed using qualitative and quantitative descriptive analysis with the calculation of the percentage of validity and practicality. The results of the study showed that the Pop Up Book learning media developed obtained a very valid category based on the validation results of linguists by 85%, material experts by 85.71%, media/design experts I by 92.85%, and media/design experts II by 100%. In addition, the results of the practicality test showed that the media obtained a very practical category with a percentage of teacher response of 95% and student response of 92.14%. The Pop Up Book media developed has an attractive visual appearance, interactive three-dimensional shapes, and materials that are tailored to the characteristics of elementary school students so that they can increase students' interest and involvement in learning. Based on the results of the research, it can be concluded that the Pop Up Book learning media for Pancasila Education is suitable for use in the learning process because it meets the category of being very valid and very practical. This media is expected to be an alternative innovative learning media to help teachers create more active, interesting, and meaningful learning at the elementary school level.